SISTEM INFORMASI PENYEWAAN DAN PEMELIHARAAN ALAT BERAT MENGGUNAKAN METODE LINEAR SEQUENCE PADA CV. SUN PASIFIC DIESEL - Selvia Mago; Abdullah; Sudirman (STMIK KHARISMA Makassar, 2018)
This research aims to design and build information system rental and maintenance of heavy equipment used to facilitate the presentation of information about the recording, controlling to calculate the cost of heavy equipment on the CV. Sun Pasific Diesel. In this information system using Linear Sequence method according to Pressman (2012) Linear Sequence Model is a classical model that is systematic, sequential in building software and this model is also often referred to as